Original paperThe effect of percutaneous mitral balloon valvuloplasty on left atrial systolic functions - Karapinar, Hekim; Emiroglu, Mehmet Y.; Aung, Soe M.; Kaya, Zekeriya; Karavelioglu, Yusuf; Kucukdurmaz, Zekeriya; Gul, Ibrahim; Esen, Ali M.; Kirma, Cevat (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2011)
Background: Conventional echocardiographic methods have already shown that successful mitral balloon valvuloplasty (MBV) can effectively increase left atrial (LA) functions. Aim : To evaluate LA functions after MBV using colour tissue Doppler imaging. Material and methods : Sixty-eight patients (58 females, mean age: 38 ±12 years) were included in the study. Within 24 h before MBV, all the patients underwent colour tissue Doppler study in addition to routine conventional echocardiographic examinations. Late diastolic velocities (A’) measured at the LA wall adjacent to the septal and lateral annuli were recorded. All the measurements were repeated 24 h after MBV. The MBV was done using the Inoue technique. Successful MBV patients were included in group A and those who developed severe mitral regurgitation (MR) were included in group B. Results: Sixty-one patients underwent successful MBV while 7 developed MR. Mitral valve areas (MVA) in both groups were significantly increased. Maximum and mean gradients, LA diameter, systolic pulmonary arterial pressure and mean LA pressures were decreased while septal and lateral A’ were significantly increased in group A. In group B, no significant change in any variable was found except for the increase in MVA. Conclusions : After successful MBV, increase in A’ velocity was seen in parallel to the recovery of LA functions. Early improvements in left atrial systolic functions after successful MBV can easily be determined by colour tissue Doppler as a quick and reliable method.